Efficacy analysis of neuroprotective drugs in patients with acute ischemic stroke based on network meta-analysis - Li, Mei; Huo, Xianhao; Chang, Qing; Liu, Xiaozhuo; Zhang, Jianning; Mao, Zhiqi (Frontiers in Pharmacology, 2024)
Objective: This network meta-analysis aimed to explore the efficacy and safety of neuroprotective agents in patients with acute ischemic stroke (AIS) and attempted to identify which drug is the most effective in improving outcomes. Methods: We searched from PubMed, Medline, Embase, Web of Science, and Cochrane library databases from the establishment of the database to June 30, 2024. Data were extracted, and the quality was assessed. The outcome measures were favorable prognosis, mortality, adverse effect. Results: A total of 35 studies were included, the total sample size was 18423 cases and included 9 interventions (citicoline, edaravone (EDV), edaravone dexborneol, cinepazide maleate, cerebrolysin, minocycline, ginkgolide, ginkgo diterpene lactone meglumine (GDLM), and conventional (CON) treatment). Our analysis revealed that excepted for edaravone dexborneol, ginkgolide, EDV, cinepazide maleate, citicoline, cerebrolysin, minocycline, and GDLM treatment schemes reduced the mortality. In terms of improving the neural function, each drug regimens significantly improved the neural function. We also found that ginkgolide, EDV, edaravone dexborneol, GDLM, cinepazide maleate treatment schemes had great total treatment effective rate. In terms of the ineffective rate, it revealed that compared with CON, edaravone dexborneol, EDV, citicoline, GDLM, ginkgolide, and cinepazide maleate treatment schemes all had a lower rate of ineffective. Finally, we analysis the rate of adverse effect, it revealed that except for cinepazide maleate and ginkgolide, EDV, minocycline, edaravone dexborneol, GDLM, citicoline, and cerebrolysin all had the higher proportion of these patients. And based on the impact of the adverse effect with different surgical interventions, we further analysis the effect by the total treatment effective rate combined with adverse effect, it revealed that EDV, ginkgolide, and edaravone dexborneol were the safest and most effective. Conclusion: In patients with AIS revealed that ginkgolide, EDV, cinepazide maleate, citicoline, cerebrolysin, minocycline, and GDLM were associcated with a reduction in mortality rates. Moreover, ginkgolide, EDV, edaravone dexborneol, and GDLM treatment schemes revealed not only a high total treatment effective rate but also a low rate of treatment inefficacy. When considering the combination of the total treatment effective rate with adverse effect, revealed that EDV, ginkgolide, and edaravone dexborneol were the safest and most effective.